The influence of annealing time on copper (II) oxide thin films using sol-gel dip-coating technique / Fatimah Zulkifli - Zulkifli, Fatimah (2016)
Copper (II) oxide (CuO) is a promising material for fabrication of photovoltaic devices such as solar cells. The objectives of this project were to deposit CuO thin films on glass substrates using sol-gel dip-coating technique and to characterize the structural, optical and electrical properties of the thin films for various annealing time. The CuO solution was prepared using sol-gel method by dissolving copper (II) acetate powder in isopropanol, diethanolamine and polyethylene glycol. The colour of the solution was dark blue. The molarity of CuO thin films was 0.25M which was deposited by using dip-coating technique on glass substrate. The annealing temperature used was 500°C with different annealing time for each sample of 30 minutes, 60 minutes, 90 minutes, 120 minutes, and 150 minutes. The samples colour were brownish-black after annealed. The surfaces morphology were checked by using Field Emission Scanning Electron Micsroscopy (FESEM). The electrical properties were measured by using two-point probe to check for the thin films resistivity. UV-vis spectrometer was used to check for the transmittance and absorbance of the thin films. Each samples' properties vary as the annealing time increases. As the annealing time increases, the grain size of the thin films increases until sample 90 minutes and started to decrease. For the transmittance percentage, as the annealing time increases, the transmittance percentage increases. The absorbance value for samples decreases as the annealing time increases. The optical band gap increases as the annealing time increases. The optical band gap obtained was in range 2.2 eV until 2.85eV. The current conducted by the samples decreases as the annealing time increases.